Parallel Computation of RCS of Electrically Large Platform with Coatings Modeled with NURBS Surfaces - Ying Yan; Wei-Xin Zhao; Xun-Wang Zhao; Yu Zhang; Chang-Hong Liang (International Journal of Antennas and Propagation)
The significance of Radar Cross Section (RCS) in the military applications makes its prediction an important problem. This paper uses large-scale parallel Physical Optics (PO) to realize the fast computation of RCS to electrically large targets, which are modeled by Non-Uniform Rational B-Spline (NURBS) surfaces and coated with dielectric materials. Some numerical examples are presented to validate this paper’s method. In addition, 1024 CPUs are used in Shanghai Supercomputer Center (SSC) to perform the simulation of a model with the maximum electrical size 1966.7 λ for the first time in China. From which, it can be found that this paper’s method can greatly speed the calculation and is capable of solving the real-life problem of RCS prediction.